Community Participation of Development in Gareccing Village Sinjai Selatan District Sinjai Regency - Nur Hadriyanti Zainal; Rifdan Rifdan; Sahade Sahade (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
Participation in village development planning meetings is important in the implementation of development in each region, where participation in Gareccing Village is still relatively low so more enthusiasm from community leaders is needed to participate in development meetings. The purpose of this study is to find out Community Participation of Development in Gareccing Village, Sinjai Selatan District, Sinjai Regency. The research method used in this study is a qualitative method with a descriptive approach. The data sources of this study are the Village Chief, Chair and Members of the Village Consultative Body (BPD), Farmers Group, Chair of the Village Community Empowerment Institution (LPMD) and Community Leaders with a total of 8 people. Data collection techniques use interviews and document review. Research results of Community Participation of Development in Gareccing Village, Sinjai Selatan District, Sinjai Regency show that in terms of community participation in village development it can work well with Participation in Decision Making, Participation in Implementation, Participation in Taking Benefits and Participation in Evaluation. Community participation in infrastructure development in Gareccing Village is quite good, because the community provides assistance in the form of energy and thought. This shows that almost all community members know and are active in a series of infrastructure development activities starting from decision making, implementation, utilization, and evaluation of each stage of development undertaken. Participation or participation is basically a form of involvement and active and voluntary participation, the growth of participation in the development process requires trust and opportunities provided by the government to the community to be actively involved in the development process. Through participation, it means truly realizing that development activities are not only obligations that must be carried out by government officials themselves, but also require community involvement. Concern and awareness and responsibility of the community regarding the importance of development which aims to improve their quality of life.